Atomic-scale investigation of MgO growth on fused quartz using angle-dependent NEXAFS measurements - Singh, Jitendra Pal; Kim, So Hee; Won, Sung Ok; Lee, Ik-Jae; Chae, Keun Hwa (ROYAL SOC CHEMISTRY, 2018)
The phenomena related to thin film growth have always been interesting to the scientific community. Experiments related to these phenomena not only provide an understanding but also suggest a path for the controlled growth of these films. For the present work, MgO thin film growth on fused quartz was investigated using angle-dependent near-edge X-ray absorption fine structure (NEXAFS) measurements. To understand the growth of MgO, sputtering was allowed for 5, 10, 25, 36, 49, 81, 144, 256, and 400min in a vacuum better than 5.0 x 10(-7) torr. NEXAFS measurements revealed the evolution of MgO at the surface of fused quartz for sputtering durations of 144, 256, and 400 min. Below these sputtering durations, no MgO was observed. NEXAFS measurements further envisaged a systematic improvement of Mg2+ ion coordination in the MgO lattice with the sputtering duration. The onset of non-interacting molecular oxygen on the surface of the sputtered species on fused quartz was also observed for sputtering duration up to 81 min. Angle-dependent measurements exhibited the onset of an anisotropic nature of the formed chemical bonds with sputtering, which dominated for higher sputtering duration. X-ray diffraction (XRD) studies carried out for sputtering durations of 144, 256, and 400 min exhibited the presence of the rocksalt phase of MgO. Annealing at 700 degrees C led to the dominant local electronic structure and improved the crystallinity of MgO. Rutherford backscattering spectrometry (RBS) and cross-sectional scanning electron microscopy (SEM) revealed a layer of almost 80 nm was obtained for a sputtering duration of 400 min. Thus, these angle-dependent NEXAFS measurements along with XRD, RBS, and SEM analyses were able to give a complete account for the growth of the thin films. Moreover, information specific to the coordination of the ions, which is important in case of ultrathin films, could be obtained successfully using this technique.
Keywords: X-RAY-ABSORPTION; THIN-FILM GROWTH; NEAR-EDGE STRUCTURE; ENERGY-LOSS SPECTRA; ELECTRONIC-STRUCTURE; FINE-STRUCTURE; MOLECULAR-ORIENTATION; ANGULAR-DEPENDENCE; METAL-OXIDES; SPECTROSCOPY